Voltage-gated potassium channels as a potential therapeutic target for the treatment of neurological and psychiatric disorders - Faulkner, Isabel E.; Pajak, Rachael Z.; Harte, Michael K.; Glazier, Jocelyn D.; Hager, Reinmar (Frontiers in Cellular Neuroscience, 2024)
Voltage-gated potassium channels are a widely distributed subgroup of potassium channels responsible for the efflux of potassium in the repolarisation of the cell membrane, and hence contribute to the latency and propagation of action potentials. As they are causal to synaptic transmission, alterations to the structure of these channels can lead to a variety of neurological and psychiatric diseases. The Kv3 subfamily of voltage-gated potassium channels are found on many neurons in the brain, including inhibitory interneurons where they contribute to fastfrequency firing. Changes to the firing ability of these interneurons can lead to an imbalance of inhibitory and excitatory neurotransmission. To date, we have little understanding of the mechanism by which excitatory and inhibitory inputs become imbalanced. This imbalance is associated with cognitive deficits seen across neurological and neuropsychiatric disorders, which are currently difficult to treat. In this review, we collate evidence supporting the hypothesis that voltage-gated potassium channels, specifically the Kv3 subfamily, are central to many neurological and psychiatric disorders, and may thus be considered as an effective drug target. The collective evidence provided by the studies reviewed here demonstrates that Kv3 channels may be amenable to novel treatments that modulate the activity of these channels, with the prospect of improved patient outcome.